Flexible particle flow‐focusing in microchannel driven by droplet‐directed induced‐charge electroosmosis. Issue 4 (29th November 2017) - Ren, Yukun; Liu, Xianyu; Liu, Weiyu; Tao, Ye; Jia, Yankai; Hou, Likai; Li, Wenying; Jiang, Hongyuan
Abstract: We report herein a novel microfluidic particle concentrator that utilizes constriction microchannels to enhance the flow‐focusing performance of induced‐charge electroosmosis (ICEO), where viscous hemi‐spherical oil droplets are embedded within the mainchannel to form deformable converging‐diverging constriction structures. The constriction region between symmetric oil droplets partially coated on the electrode strips can improve the focusing performance by inducing a granular wake flow area at the diverging channel, which makes almost all of the scattered sample particles trapped within a narrow stream on the floating electrode. Another asymmetric droplet pair arranged near the outlets can further direct the trajectory of focused particle stream to one specified outlet port depending on the symmetry breaking in the shape of opposing phase interfaces. By fully exploiting rectification properties of induced‐charge electrokinetic phenomena at immiscible water/oil interfaces of tunable geometry, the expected function of continuous and switchable flow‐focusing is demonstrated by preconcentrating both inorganic silica particles and biological yeast cells. Physical mechanisms responsible for particle focusing and locus deflection in the droplet‐assisted concentrentor are analyzed in detail, and simulation results are in good accordance with experimental observations. Our work provides new routes to construct flexible electrokinetic framework for preprocessing on‐chip biological samples before performing subsequent analysis.